(untitled) (Research, Society and Development, 2022)
The objective of this work was to determine in vitro the growth curve of Enterolobium contortisiliquum calli. Calli from E. contortisiliquum cotyledons cultivated in MS medium, supplemented with 0.5 mg L-1 2,4-D + 2.0 mg L-1 picloram + 0.5 mg L-1 kinetin + 2.0 mg L-1 BAP and repeated twice were used., at intervals of 30 days. After the second subculture, the calli growth curve was established by determining the fresh mass (mg) from the day of inoculation (time 0). The experimental design was completely randomized with 17 treatments, constituted by the evaluation intervals (0, 7, 14, 21, 28, 35, 42, 49, 56, 63, 70, 77, 84, 91, 98, 105 and 112 days), and 24 repetitions. E. contortisiliquum presented five phases of callus development: exponential, linear, deceleration, stationary and decay. The calli growth curve for the species E. contortisiliquum started with the exponential phase and remained in this phase from days 0 to 7. The linear growth period in which the cell division rate decreased and the cell area increased was observed between the days 7 and 14. While the deceleration phase occurred from 14 to 28 days. It can be concluded that the growth curve of E. contortisiliquum calli is a sigmoid with five phases and at the end of the deceleration it is time to carry out the calli subculture, on average at 28 days of in vitro culture.